Des Brésiliens dans la France des années 1820. Contribution à une histoire des mobilités transatlantiques au xixe siècle - Delphine Diaz (Amnis)
Within the framework of the « Atlantic history », this paper aims at studying the migrations and movements between the new Empire of Brazil, funded in 1822, and France during the Bourbon Restoration. At that time, the Brazilians moving to France were political exiles, banished by Dom Pedro I after the declaration of independence of the Empire. But a professional and academic mobility also strongly contributed to these migrations from Brazil to France, thanks to the appealing French system of higher education and its opening to foreign students. For other Brazilians, the stay in France during the Restoration was simply a leisure time, in Paris as well as in provincial towns, were Brazilian elites indulged in the pleasures of sea bathing and tourism. Thanks to French police records, this study will highlight that really diverse Brazilian group that stayed in France during the 1820s.